Reversed skin graft combining with lip mucosa transplantation in treating recurrent severe symblepharon: A case report. Issue 35 (August 2018) - Li, Tian; Shao, Ying; Lin, Quan; Zhang, Duo
Abstract: Rationale: Recurrent symblepharon is very difficult to cure. Techniques applied in symblepharon with no recurrence or low recurrent rate is rare and vital. Patients concerns: A 12-year-old boy with severe symblepharon caused by firework underwent 2 surgeries for treating severe symblepharon. But both surgeries were failed and symblepharon recurred. Diagnosis: He was diagnosed with conjunctival sac defect and recurrent symblepharon. Intervention: The patient received reconstruction with mucosal grafts and a reversed split-thickness skin graft, and suture upper and lower eyelids for 10 days. Outcome: Recurrent symblepharon was cured and the conjunctival sac was reconstructed. Lessons: Reversed split-thickness skin graft is much less soft compared to other materials to treat symblepharon and can be used to reconstruct conjunctival sac with no or little recurrence.